2018
DOI: 10.1097/mlr.0000000000000882
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Characteristics Associated With Postdischarge Hospital Readmission, Observation, and Emergency Department Utilization

Abstract: Including emergency department and observation stays in measures of postdischarge utilization produces similar results as measuring only readmissions in that major teaching, urban and for-profit hospitals still perform disproportionately poorly versus nonteaching or public hospitals. However, it enables identification of more outliers and a more granular assessment of the association of hospital factors and outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 24 publications
3
19
0
Order By: Relevance
“…This could be explained by the fact that patients treated in the tertiary hospitals tended to be more severe and treatment-resistant, and such severity was not fully adjusted for using the existing variables in the multi-variate model. Previous studies using data from the Centre of Medicare and Medicaid Services (CMS) in United States had identified that larger, urban, academic facilities tended to have slightly higher riskstandardized readmission rates [48,49]. In this study, tertiary hospitals in China normally had more hospital beds and higher service volumes so that the finding of this research was in line with the results of previous studies.…”
Section: Hospital Characteristicssupporting
confidence: 87%
“…This could be explained by the fact that patients treated in the tertiary hospitals tended to be more severe and treatment-resistant, and such severity was not fully adjusted for using the existing variables in the multi-variate model. Previous studies using data from the Centre of Medicare and Medicaid Services (CMS) in United States had identified that larger, urban, academic facilities tended to have slightly higher riskstandardized readmission rates [48,49]. In this study, tertiary hospitals in China normally had more hospital beds and higher service volumes so that the finding of this research was in line with the results of previous studies.…”
Section: Hospital Characteristicssupporting
confidence: 87%
“…Despite its low incidence, given the potentially lethal outcome of hospital discharge after T&A in patients with various risk factors, including clinical signs of OSA/SDB, overnight admission or prolonged postoperative monitoring is suggested in these patients. Furthermore, alterations in postoperative pain management practices with avoidance or limited use of opioids are suggested given the increased sensitivity of this patient population to the respiratory depressant effects of opioids 23,24. While there were no postoperative deaths reported in the database used for our study, the literature, and closed claims data clearly outline the risk in this patient population.…”
Section: Discussionmentioning
confidence: 85%
“…This study suggests the need to better understand and account for the involvement of the ED in quality measurement for care coordination and population health management strategies within communities and health systems, 47 particularly those involving hospital readmissions. Policy makers may wish to adopt proposals 48,49 to incorporate ED utilization and observation stays into the HRRP to improve its reliability by better accounting for statistical outliers and reducing possible unintended consequences. Another possibility is to develop an explicit ED revisit measure that assesses readmissions, mortality, and morbidity after ED revisits.…”
Section: Discussionmentioning
confidence: 99%